Successful simultaneous liver‐kidney transplantation for renal failure associated with hereditary complement C3 deficiency. Issue 8 (6th February 2020) - Nayagam, Jeremy S.; McGrath, Samuel; Montasser, Mahmoud; Delaney, Michael; Cairns, Tom D.; Marchbank, Kevin J.; Denton, Harriet; Yang, Yi; Sacks, Steven H.; Cook, H Terry; Shah, Sapna; Heaton, Nigel; et al.
Abstract : Hereditary complement C3 deficiency is associated with recurrent bacterial infections and proliferative glomerulonephritis. We describe a case of an adult with complete deficiency of complement C3 due to homozygous mutations in C3 gene: c.1811delT (Val604Glyfs*2), recurrent bacterial infections, crescentic glomerulonephritis, and end‐stage renal failure. Following isolated kidney transplantation he would remain C3 deficient with a similar, or increased, risk of infections and glomerulonephritis. As C3 is predominantly synthesized in the liver, with a small proportion of C3 monocyte derived and kidney derived, he proceeded to simultaneous liver‐kidney transplantation. The procedure has been successful with restoration of his circulating C3 levels, normal liver and kidney function at 26 months of follow‐up. Simultaneous liver‐kidney transplant is a viable option to be considered in this rare setting. Abstract : The authors describe a case of a patient with hereditary complement C3 deficiency and end‐stage renal failure who underwent simultaneous liver and kidney transplantation, which successfully restored normal circulating C3 levels with normal allograft function.